Diagnostic imaging of benign and malignant neck masses in children—a pictorial review - Brown, Ruth Elizabeth; Harave, Srikrishna (Quantitative Imaging in Medicine and Surgery; Vol 6, No 5 (October 31, 2016): Quantitative Imaging in Medicine and Surgery (Pediatric Neuro-radiology: Clinical Topics and Technical Development), 2016)
Neck masses are frequently encountered in pediatric medicine, and can present a diagnostic dilemma for the clinicians involved. There are several means by which neck masses in children can be subdivided, for example by age at presentation, anatomical location including compartments and fascia of the neck, their classical appearance when imaged, or by etiology. When imaging children the clinicians must be mindful of radiation exposure and as such ultrasound (US) is often attempted first. Cross sectional imaging can be helpful for problem solving with CT being particularly useful for assessing the patient in more acute scenarios, for example when there is airway compromise. Nuclear medicine scintigraphy has a role in specific circumstances and can aid in staging in the presence of malignancy. If required, additional acquisition by means of magnetic resonance imaging (MRI) and computed tomography (CT) can be considered. This pictorial review describe the diagnostic imaging of (I) congenital and Developmental Pathologies, including thyroglossal duct cyst, branchial cleft cyst, cystic hygroma, dermoid cyst, thymic cyst and ectopic thymus; (II) neoplastic lesions, including hemangiomas and vascular malformations, pilomatrixoma, neurofibroma, neuroblastoma, rhabdomyosarcoma, papillary thyroid cancer, lymphoma & leukemia; (III) neck masses of Infective causes, including lymphadenitis, retropharyngeal and peritonsilar abscess, salivary gland inflammation; and (IV) other miscellaneous lesions, including ranula, sternocleidomastoid fibromatosis coli, and goiter. Neck masses are common in the pediatric population with a broad and varied differential; malignant etiologies are less frequently encountered when compared with adults but an awareness of its potential is important when reviewing imaging.